The effect of China's new cooperative medical scheme on health expenditures among the rural elderly - Yanbing Zeng; Jiajing Li; Zhipeng Yuan; Ya Fang (BMC, 2019)
Abstract Background The alarming progression of an increasingly aging population in China has attracted much attention within the country and abroad. In 2003, the Chinese central government launched the New Cooperative Medical Scheme (NCMS) to resolve problems of healthcare inequity in regions with inadequate infrastructure and relative poverty. The purpose of this study was to investigate the effect of NCMS on health expenditures by the Chinese rural elderly population. Methods The data were obtained from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), which was conducted in 2005, 2008, 2011 and 2014. Elderly people living in rural areas and 60 years old or above were screened for the investigation. The sample size was 7472 in 2005, 11,705 in 2008, 9239 in 2011, and 6059 in 2014. The OOP% and reimbursement ratio were the medical expenses paid by individuals accounting for their per capita annual income and the medical expenses paid by medical insurance accounting for their total medical expenses, respectively. By controlling for individuals' sociodemographic characteristics, pensions, demands and utilization of health services, we estimated the effect of the NCMS on the OOP% and reimbursement ratio for the rural elderly using seemingly unrelated regression (SUR). Results The NCMS coverage ranged from 11.63% in 2005 to 80.34% in 2014. The medical expenses of the elderly also increased from an average of $204.77 in 2005 to $696.23 in 2014, which was more than three times as much as in 2005. From 2005 to 2014, the reimbursement ratio for medical expenses of rural elderly people with NCMS increased significantly from 30.6% in 2005 to 56.1% in 2014. The proportion of reimbursement ratio for rural seniors with NCMS increased by 6.4% across each survey cycle (every 3 years). However, the NCMS resulted in an insignificant decrease in OOP% by 1.4% across each survey cycle (every 3 years). Among other medical insurances, public insurance and private elder insurance had significant positive impacts on reimbursement ratio but did not influence OOP%. Conclusions NCMS remarkably increased the rural elderly's reimbursement ratio but insignificantly decreased the rural elderly's OOP%. In addition, the proportion of reimbursement ratio for NCMS participants increased by 6.4% every 3 years. Lower outpatient reimbursement, migration, limited reimbursement scope, an increasing demand for medical services and the rapid growth of medical expenses may be reasons for the gaps between the nominal reimbursement ratio and the actual reimbursement ratio and OOP%. Policymakers should further modify NCMS policies in rural China.